NATO Standards and Practice for Munitions Safety and Insensitive Munitions - Ernest BAKER (Problemy Mechatroniki, 2018)
The NATO Munitions Safety Information Analysis Center (MSIAC) is a multinational collaboration that collects, stores, and analyses technical information related to Munitions Safety (MS) and Insensitive Munitions (IM). MSIAC supports its member nations through a variety of products and services. Poland is becoming a MSIAC member nation during 2018. MSIAC has a diverse programme of work aimed at developing and sharing the related underpinning scientific knowledge. This is then applied to support policy implementation and development related to munition safety. This paper provides an overview of: NATO policies for MS related to the storage and transport of munitions; NATO IM requirements and testing; and how they relate to Poland. In particular, a comparison of NATO munitions storage policy with Poland munitions storage regulations has identified some differences. These differences are discussed.